An Examination of the Feasibility of Detecting Cocaine Use Using Smartwatches - Ertin, Emre; Sugavanam, Nithin; Holtyn, August F.; Preston, Kenzie L.; Bertz, Jeremiah W.; Marsch, Lisa A.; McLeman, Bethany; Shmueli-Blumberg, Dikla; Collins, Julia; King, Jacqueline S.; McCormack, Jennifer; Ghitza, Udi E. (Frontiers in Psychiatry, 2021)
As digital technology increasingly informs clinical trials, novel ways to collect study data in the natural field setting have the potential to enhance the richness of research data. Cocaine use in clinical trials is usually collected via self-report and/or urine drug screen results, both of which have limitations. This article examines the feasibility of developing a wrist-worn device that can detect sufficient physiological data - i.e., heart rate and heart rate variability - to detect cocaine use. In addition to device development, this study aimed to characterize the conditions under which high quality data could be gathered in the natural field setting among cocaine users via smartwatch devices that were less obtrusive than chestband measures used in prior research. The study also aimed to further develop a cocaine use detection algorithm used in previous research with an electrocardiogram on a chestband by adapting it to a photoplethysmography sensor on the wrist-worn device which is more prone to motion artifacts. Results indicate that wrist-based heart rate data collection is feasible and can provide higher data yield than chest-based sensors, as wrist-based devices were also more comfortable and affected daily lives less often than chest-based sensors. When properly worn, wrist-based sensors produced similar quality of heartrate and heartrate variability features to chest-based sensors and matched their performance in automated detection of cocaine use events.